Optimization of Process Variables and Validation of The Models for Nano-Particle Embedded Biodegradable Polymers for Packaging - Gautam, Rakesh Babu; Kumar, Satish; Kalia, Anu (International Journal of Bio-resource and Stress Management, 2020)
The aim of this work was to develop antimicrobial biodegradable polymeric films based on whey and soy protein isolate and titanium dioxide nano powder. Five levels of sonication 20%, 40%, 60%, 80% and 100%.When TiO2 was incorporated into a polymer matrix of a packaging material, it provided protection from food borne microorganism as well as odour staining deterioration and allergens due to presence of radiation of relative low wavelength near the ultraviolet region. The TiO2 film exhibits excellent mechanical and chemical durability. Experimental design and data analysis: Statistical package Design-Expert Version 7.0 (Statease Inc., Minneapolis, MN, USA) was used to design the experiment. The central composite design CCRD for three independent variables was performed. The independent variables considered were pH (A) Sonication levels (B). The levels of each variable were established based on the results of earlier experiments and preliminary trials A rotatable, central composite design was employed to determine the film formation conditions. Effect of sonication on color and strength of biopolymers film was examined. The predicted values and experimental values were analysed by using different models. The experiments were repeated at optimized values of process variables. The film was then tested for differential scanning calorimetric (DSC), scanning electron microscopy (SEM), film forming and melting temperature (Tm) etc. The predicted and experimental values were statistically analysed for model validation. The film was used for individual packaging and storage of guava and tomato under ambient and cold storage conditions.